Traumatic, Old, and Unreduced Bilateral Knee Dislocation: A Case Study and Literature Review - SM Javad Mortazavi (Journal of Orthopedic and Spine Trauma, 2020)
Background: Old unreduced knee dislocation is rare, which means the experience is still lacking about the best treatment options. Moreover, several surgical options for this condition are still lacking in peer-reviewed research. This is a case report of the treatment of a patient who had bilateral traumatic knee dislocations that were unreduced two months after injury. Case Presentation: A 45-year-old man with bilateral traumatic unreduced knee dislocation came 2 months after injury. He had no active knee extension and was unable to walk. He underwent open reduction and external fixation. He had a good range of motion (ROM) and painless walking in short term. After 5 years, he had acceptable ROM and painless walking, but x-rays showed persistent posterior subluxation of the left knee and some bone loss of the right tibia. Conclusions: Open reduction, repair of torn ligaments, and external fixation was an effective treatment in regaining ROM and stability in a patient who had bilateral unreduced knee dislocations of two months duration. After five years, the patient had a satisfactory function, but radiographs showed persistent posterior subluxation of one knee and some bone loss of the tibia in the other